Behavioral Programming. (Communications of the ACM, 2012)
The article considers behavioral programming in computer programming and software development. Behavioral programming is defined as an extension of programming based on the the use of scenarios in computer programming. The ability of behavioral programming to allow multi-model scenarios in coding applications is considered. The use of the Java programming language in behavioral programming is discussed. Methodologies for verification and debugging of behavioral programs are examined. The use of behavioral programming in feature-oriented software development is considered.